LITERATURE REVIEW: INTERNALISASI METODE STORY TELLING BERBASIS KURIKULUM CINTA SEBAGAI STRATEGI PEMBELAJARAN - Arsya Ma’wa Ni’matul Izzati; Sofiatun Anisa; Reva Nur Aqila; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is not only focused on the acquisition of knowledge but also on the development of students' character. One effort that can support this goal is the implementation of the storytelling method based on the Love Curriculum in the learning process. This article aims to examine the internalization of the storytelling method based on the Love Curriculum as a learning strategy that can instill moral, social, and spiritual values in students. This study employs a literature review method by analyzing various journals, books, and relevant scientific sources related to value internalization, the storytelling method, and the Love Curriculum. The findings indicate that the storytelling method can enhance students' emotional engagement, develop empathy, and facilitate the understanding of values embedded in stories. Meanwhile, the Love Curriculum emphasizes the importance of compassion, tolerance, care, and respect for others within the educational process. The integration of the storytelling method and the Love Curriculum can create a more humanistic and meaningful learning environment, thereby supporting character development and encouraging the application of positive values in students' daily lives.